2020
DOI: 10.1017/s1368980020004954
|View full text |Cite
|
Sign up to set email alerts
|

Exploring healthcare professionals’ views of the acceptability of delivering interventions to promote healthy infant feeding practices within primary care: a qualitative interview study

Abstract: Objective: Early-life nutrition plays a key role in establishing healthy lifestyles and preventing chronic disease. This study aimed to (1) explore healthcare professionals’ (HCP) opinions on the acceptability of and factors influencing the delivery of interventions to promote healthy infant feeding behaviours within primary care and (2) identify proposed barriers/enablers to delivering such interventions during vaccination visits, to inform the development of a childhood obesity prevention intervention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…The TFA comprises seven constructs 13 (Table 1 presents TFA constructs and definitions). The TFA has been used successfully in other (nonsurgical) contexts to identify components that could be addressed to enhance acceptability, such as nurse‐led reviews of inflammatory rheumatological conditions, postnatal exercise and infant feeding practices 14–16 . It has also been applied in a small number of surgical contexts such as maternal–foetal surgery and intravitreal injections for macular degeneration 17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TFA comprises seven constructs 13 (Table 1 presents TFA constructs and definitions). The TFA has been used successfully in other (nonsurgical) contexts to identify components that could be addressed to enhance acceptability, such as nurse‐led reviews of inflammatory rheumatological conditions, postnatal exercise and infant feeding practices 14–16 . It has also been applied in a small number of surgical contexts such as maternal–foetal surgery and intravitreal injections for macular degeneration 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…The TFA has been used successfully in other (nonsurgical) contexts to identify components that could be addressed to enhance acceptability, such as nurse‐led reviews of inflammatory rheumatological conditions, postnatal exercise and infant feeding practices. 14 , 15 , 16 It has also been applied in a small number of surgical contexts such as maternal–foetal surgery and intravitreal injections for macular degeneration. 17 , 18 The TFA has not yet been used in acceptability studies relating to arthroplasty or short‐stay models of care.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have identified factors which are associated with the success of parenting programmes including parental attitudes towards programme content, changes in parenting skills and confidence, and positive experiences of the group process (26)(27)(28). In the context of early child nutrition, group-based programmes focusing on complementary feeding, or 'weaning workshops', have been suggested as a promising approach to target infant feeding practices (12,21,23,24,29,30). Such programmes are workshop-style events that can target several important aspects for effective community-based interventions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Primary care represents a promising setting for such interventions given its community-based context and an increasing global focus on health promotion and disease prevention within primary care practice (18)(19)(20) . Given their expertise, community dietitians may have an important role to play in interventions that aim to improve healthy infant feeding; however, recent research has highlighted limited capacity amongst dietitians to prioritise preventive-focused interventions over complex clinical issues such as feeding challenges or problems (21) .…”
mentioning
confidence: 99%
“…Other studies have identified factors which are associated with the success of parenting programmes including parental attitudes towards programme content, changes in parenting skills and confidence and positive experiences of the group process (26)(27)(28) . In the context of early child nutrition, group-based programmes focusing on complementary feeding, or 'weaning workshops', have been suggested as a promising approach to target infant feeding practices (10,21,23,24,29,30) . Such programmes focus on individualor family-level behaviour change through a number of home visits, individual counselling or group sessions in a clinical or community setting targeting several important aspects e.g.…”
mentioning
confidence: 99%